An Alternative Approach to Linguistic Theories of Language Acquisition: Focus on The Cognitive Theory - El-Dali, Hosni M. (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
Although linguistics provides a useful perspective on L2 learning, it must be remembered that linguistics is only one of the disciplines that SLA research can draw on. With this in mind, this study provides a thumbnail sketch of some currently prevalent theories which try to explain how foreign languages are learned. It, also, spells out some alternatives to the linguistics-based approach to foreign language acquisition research. More specifically, some limitations of linguistic theories in addressing the role of mental processes in L2 acquisition are identified and recent theoretical developments in cognitive psychology that can be applied to L2 acquisition are outlined. Moreover, this study reports the results of an empirical investigation carried out by the author on 200 Egyptian University students enrolled in the department of English, Faculty of education, Minufiya University. They were divided into two groups according to their academic status: 1) Beginners (N=100); and 2) Advanced learners (N=100). It attempts to answer three interrelated questions: 1) to what extent does the advanced students’ performance in listening tasks differ from that of the beginning students before and after training? 2) how can two types of training (intensive listening vs. improving learners’ linguistic skills) affect L2 learners’ listening comprehension skill?, and 3) what does students’ performance, before and after the training, tell us about their abilities to transfer? The instruments used are (1) pre-test; (2) classroom instruction sessions; (3) post-test, and (4) interviews. The data analysis has a quantitative and a qualitative, interpretative part. Results are obtained and discussed, and pedagogical applications are suggested.